Brothas be, yo like George, ain't that funkin' kinda hard on you? - Clinton, George 1941-; Greenman, Ben (Aria Books, 2014)
Traces the funk music legend's rise from a 1950s barbershop quartet to an influential multigenre artist, discussing his pivotal artistic and business achievements with "Parliament-Funkadelic."
Includes bibliographical references, discography, and index
Introduction: let's take it to the stage (1978) -- The bomb -- If you hear any noise, it's just me and the boys -- I'm into something and I can't shake it loose -- Friends, inquisitive friends, are asking what's come over me -- Sound a little something like raw funk to me -- Open up your funky mind and you can fly -- Would you like to dance with me? We're doing the cosmic slop -- Everybody get up for the down stroke -- There's a whole lot of rhythm goin' round -- Put a glide in your stride and a dip in your hip and come on up to the mothership -- When the syndrome is around, don't let your guard down -- So high you can't get over it -- Never missin' a beat -- You can walk a mile in my shoes, but you can't dance a step in my feet -- The dog that chases its tail will be dizzy -- Rhythm and rhyme, rhythm and rhyme, rhythm and motherfucking rhyme -- If anybody gets funked up, it's gonna be you -- You gonna get ate
Keywords: Clinton, George / 1940-; Funkadelic (Musical group); Parliament (Musical group); Funk musicians / United States / Biography; USA; Biografie